Investigating the effect of imikode virtual reality game in enhancing object oriented programming concepts among university students in Nigeria - Sunday, Kissinger; Wong, Seng Yue; Samson, Balogun Oluwafemi; Sanusi, Ismaila Temitayo (Education and information technologies, 2022)
Learning object oriented programming (OOP) has been a daunting and challenging task for students across tertiary institutions in Nigeria. Various literatures have suggested the use of technology as a way to improve students’ understanding of the subject. In this study, the overall aim is to investigate the effect of Imikode- a virtual reality (VR) game amongst students of higher educational institutions in Nigeria studying object oriented programming courses and whether there is a positive correlation in their understanding of the subject on one hand and also an improvement in their programming skills on the other hand. First year computer science students across tertiary institutions in Nigeria were recruited to play the game after which the usefulness, satisfaction and ease of use questionnaire was administered. The results of the survey showed a positive correlation in their understanding of the subject and a further booster in their programming skills. Furthermore, the qualitative data analyzed showed how the Imikode tool motivated students in learning OOP concepts and thus, enabling more engagement with the technology as a veritable tool for learning OOP concepts.